Non invasive and surgical measurement of length of soft tissue from the tip of interdental papilla to the alveolar crest - Rajashri A. Kolte; Abhay P. Kolte; Pallavi S. Ghodpage (Elsevier, 2013)
Background: Various methods, including clinical and radiographic techniques, can be used to assess periodontal regeneration in interproximal areas. The goal of the present study was to compare the papilla length relative to the alveolar bone crest measured by clinical, intrasurgical, and radiographic techniques. Materials and methods: The study sample included 250 interproximal papillae in 68 patients with generalized chronic periodontitis. The papilla length from the alveolar bone crest was measured clinically (as the actual papilla length, APL), intrasurgically (as the bone probing length, BPL), and radiographically (as the radiographic bone length, RBL). Measurements were standardized by using acrylic resin stents, XCP rinn, a paralleling technique, and/or a radiographic grid. Results: The mean (± standard deviation) for RBL was 4.9 ± 0.8 mm, BPL was 5.1 ± 0.6 mm, and APL was 5.1 ± 0.6 mm. Correlations between RBL and APL and between BPL and APL were 0.918 and 0.943, respectively (both P < 0.01). Conclusions: If the clinical recordings are appropriately standardized, then noninvasive radiographic methods can be used to evaluate the papilla length with good accuracy. Keywords: Interproximal papilla, Periodontal regeneration, Radiographic bone length, Bone probing length, Actual papilla length